An analysis of Ariel’s fulfillment of needs in The Little Mermaid (2023) film - Fachryan, Farhan; Ariani, Setya; Amalia, Puji Astuti (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
In a world where not all desires can be fulfilled, Ariel attempts to overcome those limitations in any way she can. The Little Mermaid (2023) tells the story of a young mermaid who dreams of living in the human world. Her desire for acceptance and curiosity about life on land drive her to defy the norms and rules of the underwater kingdom. Through the narrative of this story, this study aims to analyze Ariel’s fulfillment of needs based on Maslow’s hierarchy of needs, ranging from physiological needs to self-actualization. Additionally, the study explores the application of this theory in examining character development in literary works. This research uses qualitative content analysis to investigate Ariel’s psychological experiences and her character development. Characterization theory and plot structure are utilized to trace Ariel’s character transformation and reveal how each stage of need manifests throughout the storyline. The results indicate that Ariel successfully fulfills all five levels of needs, with the need for love and belonging emerging as the most dominant driving force behind her decisions and transformation. Her strong attachment to the human world and longing for acceptance lead her to take significant risks, which allow her to fulfill her needs progressively, from the most fundamental to the highest level of self-actualization.